The influence of the mandibular gonial angle on the occurrence of mandibular angle fracture. Issue 3 (3rd April 2019) - Dhara, Vasantha; Kamath, Abhay T.; Vineetha, Ravindranath
Abstract: Background/Aims: Angle fractures represent the largest percentage of mandibular fractures. They pose as a unique entity because of their codependent morphological dynamic factors, rendering the understanding of the mechanism, and treatment challenging. The aim of this study was to analyze the association between the mandibular gonial angle and the risk of mandibular angle fracture while highlighting its clinical relevance. Materials and Methods: A retrospective analysis of radiographs of patients treated for mandibular fractures was done. The factors studied were as follows: the presence of a high gonial angle and an impacted third molar. The outcome was mandibular angle fracture. The gonial angle was measured using Planmeca Digital Software 3.7.0.R. Status of the third molar was also noted. Data obtained were analyzed using SPSS 22 (IBM Corp, Armonk, NY). Results: The sample comprised 70 mandibular fractures (32 angle fractures and 38 non‐angle fractures). The mean gonial angle in the angle fracture group was 128.5 ± 5.4º which was 10.2° larger than in the non‐angle group (mean 118.5 ± 4.4º; P  = 0.0001). Patients with a high gonial angle were 8.7 times more likely to sustain an angle fracture than those with normal or low gonial angles. A statistically significant relationship between the presence of impacted third molar and patients sustaining mandibular angle fractures was noted ( P  = 0.0001). Conclusion: Subjects with a high gonial angle and an impacted third molar are at an increased risk for mandibular angle fracture due to direct and indirect morphological factors.